MANAGEMENT OF THE KITAB KUNING LEARNING HABITUATIONPROGRAM VIA THE SOROGAN METHOD AT THE MADRASAH ALIYAH LEVEL - Mohammad Nashih; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze the management of the Kitab Kuning learning habituation program through the sorogan method in Madrasah Aliyah as an effort to strengthen religious literacy competencies and book reading skills for students. The implementation of the sorogan method in the madrasah aliyah environment is a pedagogical innovation that integrates pesantren traditions with the formal education system. This study uses a qualitative approach with a literature study design. Data were collected from several literature sources, such as books and scientific articles. Data analysis was carried out through the stages of data reduction, data presentation, and systematic conclusion drawing. The results of the study show that the management of the Kitab Kuning learning habituation program through the sorogan method in madrasah aliyah is carried out through four management functions, namely: (1) planning, which includes setting objectives, integrating the program into the local content curriculum or extracurricular activities, preparing a regular schedule, and determining the books according to the students' ability levels; (2) organization through the division of tasks among supervising teachers and the grouping of students; (3) implementation that emphasizes individual reading practice in front of the teacher, immediate correction, and reinforcement of nahwu and sharaf rules; and (4) evaluation through periodic assessment of reading fluency, accuracy of i'rab, and understanding of meaning. Habituation programs are effective as a strategy for strengthening religious and academic character in Islamic high schools.